Besonderheiten in der Nachsorge von gastrointestinalen Tumoren - Artzner, Kerstin; Malek, Nisar Peter (DMW - Deutsche Medizinische Wochenschrift, 2018)
Treatment for gastrointestinal malignancies has evolved over the past two decades. Long-term outcomes have considerably improved, however a high rate of recurrence persists. With the exception of colon cancer, clear consensus strategies with regards to post-treatment surveillance are lacking. Current surveillance practices in non-colon cancer cases are inadequately based on retrospective case analyses and expert recommendations which are not uniformly consistent.This article presents the key follow-up aspects such as recurrence frequency, timing, localization, and therapeutic efficacy for the most common gastrointestinal tumors, and summarizes current recommendations for early detection of recurrence. In particular, we compare and contrast the recommendations of the German S3 guideline, the European Society for Medical Oncology (ESMO) and the American National Comprehensive Cancer Network (NCCN).
Keywords: Nachsorge; Tumornachsorge; Follow-up; Rezidiv; Rezidivfrüherkennung; Früherkennung; Screening; Karzinom; Krebs; Tumor; Empfehlung; S3-Leitlinie; ESMO; NCCM; Fachgesellschaften; gastrointestinale Tumore; Ösophaguskarzinom; Magenkarzinom; HCC; Hepatozelluläres; Pankreaskarzinom; Kolonkarzinom; Rektumkarzinom; Kolorektales Karzinom